Si Ferriols, ang Katamaran ng Pag-iisip, at ang Alaala ng Meron - Rodriguez, Agustin Martin G (Archīum Ateneo, 2018)
: This study explores Roque J. Ferriols’s ideas of “pakikitagpo sa Meron” (opening to Being) and “paggising ng alaala ng Meron” (awakening of the memory of Being) and their implications for research and scholarship in philosophy. It argues that the abstraction and systematization that has become the norm of academic philosophical writing is not adequate to the genuine opening to the presencing of Being. Ferriols’s own style of writing and thinking demonstrates a more indigenous form of philosophizing that makes possible what the calls the awakening of the remembrance of Being in the person’s deepest consciousness.